2014
DOI: 10.1136/ejhpharm-2013-000439
|View full text |Cite
|
Sign up to set email alerts
|

Parents and carers of patients who had liver transplants: opinions and experiences of medication issues

Abstract: Purpose Birmingham Children's Hospital in the UK provides family centred care for post-transplant medication (PTM) management. Nevertheless, PTM is often considered a burden for patients, and can be difficult to manage. This study was designed to identify the main medication issues encountered by children and their parents in order to find suitable means to improve their care management. Method Anonymised multifactorial, cross-sectional, single-site survey. Parents of children transplanted from January 2011 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The questionnaire covered the following topics: medication reviews, reported adherence, information requests, adverse effects, administration and obtaining medication supplies. The questions were developed by the authors based on the aspects covered by the NMS and MUR services, previous published experiences . and the authors’ knowledge of managing medication use in paediatric patients.…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…The questionnaire covered the following topics: medication reviews, reported adherence, information requests, adverse effects, administration and obtaining medication supplies. The questions were developed by the authors based on the aspects covered by the NMS and MUR services, previous published experiences . and the authors’ knowledge of managing medication use in paediatric patients.…”
Section: Methodsmentioning
confidence: 90%
“…The questions were developed by the authors based on the aspects covered by the NMS and MUR services, previous published experiences. [2][3][4]13] and the authors' knowledge of managing medication use in paediatric patients.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations